Current Status and Security Trend of OSINT. (18th February 2022) - Hwang, Yong-Woon; Lee, Im-Yeong; Kim, Hwankuk; Lee, Hyejung; Kim, Donghyun
Abstract : Recently, users have used open-source intelligence (OSINT) to gather and obtain information regarding the data of interest. The advantage of using data gathered by OSINT is that security threats arising in cyberspace can be addressed. However, if a user uses data collected by OSINT for malicious purposes, information regarding the target of an attack can be gathered, which may lead to various cybercrimes, such as hacking, malware, and a denial-of-service attack. Therefore, from a cybersecurity point of view, it is important to positively use the data gathered by OSINT in a positive manner. If exploited in a negative manner, it is important to prepare countermeasures that can minimize the damage caused by cybercrimes. In this paper, the current status and security trends of OSINT will be explained. Specifically, we present security threats and cybercrimes that may occur if data gathered by OSINT are exploited by malicious users. Furthermore, to solve this problem, we propose security requirements that can be applied to the OSINT environment. The proposed security requirements are necessary for securely gathering and storing data in the OSINT environment and for securely accessing and using the data collected by OSINT. The goal of the proposed security requirements is to minimize the damage when cybercrimes occur in the OSINT environment.